Desain Gamifikasi sebagai Pelengkap Aplikasi Pembelajaran Sistem Pendukung Keputusan Klinis - Dhias Muhammad Naufal; Adhistya Erna Permanasari Permanasari; Paulus Insap Santosa; Silmi Fauziati; Indriana Hidayah (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2024)
In the learning process, learning media supports the delivery of educational material to students. Implementing gamification enriches educational media and enhances student engagement. This research developed e-learning media for clinical decision support systems (CDSS) material. In the medical field, CDSS is well established and integrated into education as part of the curriculum. CDSS is a computerized system aiding decision-making in diagnosing and treating diseases. In the educational domain, CDSS courses are offered to clinical and nonclinical students. The application was developed using a feature-driven development method and incorporated gamification elements like rewards, challenges, and leaderboards through MDA frameworks. The development process began with the overall design of the application and the determination of learning objectives, followed by the integration of gamification elements aligned with the application’s design. The development included application design, gamification elements, functionality, usability, and user experience testing aspects. The final product is an Android application. Functionality testing using black box testing achieved 100% suitability. User testing was conducted using the system usability scale (SUS) and the user experience questionnaire (UEQ). The results showed an average SUS score of 74.9, indicating good usability, and the UEQ score was rated “Excellent.” These findings demonstrate that incorporating gamification in CDSS learning enhances the application’s supporting features. Gamification elements such as rewards, challenges, and leaderboards are expected to attract learners and encourage active participation in the learning process. CDSS learning applications have the potential to increase motivation and engagement, creating an interesting and effective learning experience for individuals from various backgrounds.